Observation of a resonance in B+ → K+ μ+ μ- decays at low recoil. - Aaij, R; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; Alkhazov, G; Alvarez Cartelle, P; et al. (2013)
A broad peaking structure is observed in the dimuon spectrum of B+ → K+ μ+ μ- decays in the kinematic region where the kaon has a low recoil against the dimuon system. The structure is consistent with interference between the B+ → K+ μ+ μ- decay and a resonance and has a statistical significance exceeding six standard deviations. The mean and width of the resonance are measured to be 4191(-8)(+9)  MeV/c2 and 65(-16)(+22)  MeV/c2, respectively, where the uncertainties include statistical and systematic contributions. These measurements are compatible with the properties of the ψ(4160) meson. First observations of both the decay B+ → ψ(4160)K+ and the subsequent decay ψ(4160) → μ+ μ- are reported. The resonant decay and the interference contribution make up 20% of the yield for dimuon masses above 3770  MeV/c2. This contribution is larger than theoretical estimates.